"Click" Chemistry Mildly Stabilizes Bifunctional Gold Nanoparticles for Sensing and Catalysis. Issue 27 (30th May 2014) - Li, Na; Zhao, Pengxiang; Liu, Na; Echeverria, María; Moya, Sergio; Salmon, Lionel; Ruiz, Jaime; Astruc, Didier
Abstract A large family of bifunctional 1, 2, 3‐triazole derivatives that contain both a polyethylene glycol (PEG) chain and another functional fragment (e.g., a polymer, dendron, alcohol, carboxylic acid, allyl, fluorescence dye, redox‐robust metal complex, or a β‐cyclodextrin unit) has been synthesized by facile "click" chemistry and mildly coordinated to nanogold particles, thus providing stable water‐soluble gold nanoparticles (AuNPs) in the size range 3.0–11.2 nm with various properties and applications. In particular, the sensing properties of these AuNPs are illustrated through the detection of an analogue of a warfare agent (i.e., sulfur mustard) by means of a fluorescence "turn‐on" assay, and the catalytic activity of the smallest triazole–AuNPs (core of 3.0 nm) is excellent for the reduction of 4‐nitrophenol in water.